Evaluation of different irrigation solutions and activation methods on removing calcium hydroxide - KARTAL, NEVİN; CİMİLLİ, ZÜHRE HALE (ELSEVIER TAIWAN, 2021)
Background/purpose: Dual Rinse HEDP is a soft chelator which can be used simultaneously with sodium hypochlorite (NaOCl). The aim of this study is to evaluate the efficacy of Dual Rinse HEDP with different irrigation systems on removing calcium hydroxide [Ca(OH)(2)]. Materials and methods: Eighty maxillary central incisor teeth were shaped and a standard groove on the apical third of the root canal surface was prepared. The root canals were filled with Ca(OH)(2). Samples were divided into two groups according to the solution and these two groups were divided into three subgroups based on the activation technique. In group 1 (n = 10) Ca(OH)(2) was removed using conventional irrigation with NaOCl whereas in group 2 (n = 10) conventional irrigation with NaOCl - Dual Rinse HEDP mixture was used. Group 3 (n = 15) and group 4 (n = 15) received sonic activation with the same irrigants as groups 1 and 2 respectively. In group 5 (n = 15) passive ultrasonic irrigation (PUI) was used with NaOCl while in group 6 (n = 15) the irrigant was the mixture. The amount of remaining Ca(OH)(2) in the artificial grooves were evaluated under a light microscope. Results: None of the procedures managed to completely remove the Ca(OH)(2) from artificial grooves. There was no significant difference between the groups (p = 0.053). The scores were significantly lower in PUI group compared to the other techniques between NaOCl groups (p = 0.021). Conclusion: Dual Rinse HEDP does not make a difference on elimination of Ca(OH)(2). PUI is more efficient than both methods when NaOCl solution is used. (C) 2020 Association for Dental Sciences of the Republic of China. Publishing services by Elsevier B.V.
Keywords: Endodontics; Calcium hydroxide; Etidronic acid; Ultrasonics; Sodium hypochlorite